Nnd Haiku: - Donna Laurent Caruso (Dawnland Voices, 2017)
ANCC-accredited nursing continuing professional development providers must evaluate activities and aggregate outcomes to demonstrate mission alignment, learner impact, and program effectiveness. Open-ended evaluations offer valuable insights but are often underused because manual analysis is time-consuming and inconsistent. This practice innovation uses generative artificial intelligence as a decision-support tool to improve efficiency and consistency in qualitative evaluation, reducing administrative burden, strengthening the use of learner feedback, and supporting more data-informed activity and provider-level planning.